Digital Forensic Investigation Challenges based on Cloud Computing Characteristics - Narayana Samy, Ganthan; Maarop, Nurazean; Shahidan Abdullah, Mohd; Perum, Sundresan; Hasan Albakri, Sameer; Shanmugam, Bharanidharan; Jeremiah, Premylla (International Journal of Engineering and Technology, 2018)
One of the most popular computing technologies is cloud computing. There are many benefits in adopting cloud computing such as high-performance, flexibility and availability on-demand, more focused on the business objective and low-cost. However, the characteristics of the cloud computing environment have created many difficulties and challenges for digital forensic investigation processes. Therefore, this paper focuses on the digital forensic investigation challenges based on cloud computing characteristics.Â Â